Taxonomic Composition of Protist Communities in the Coastal Stratified Lake Kislo-Sladkoe (Kandalaksha Bay, White Sea) Revealed by Microscopy - Yulia V. Mindolina; Elena A. Selivanova; Marina E. Ignatenko; Elena D. Krasnova; Dmitry A. Voronov; Andrey O. Plotnikov (Diversity, 2022)
Lake Kislo-Sladkoe is a stratified water body partly isolated from the White Sea. Perennial meromixis in the lake irregularly alternates with mixing events. Taking into account that the protists of Arctic coastal stratified water bodies are understudied, we evaluated for the first time the vertical structure, species richness, and diversity of protists assigned to different taxonomic groups in Lake Kislo-Sladkoe using light, luminescent, and scanning electron microscopy. To test the research hypothesis that a mixing event affects the vertical stratification and species composition of protists in a stratified lake, we compared the protist communities of Lake Kislo-Sladkoe in two extremely different states: strong meromixis vs. full vertical mixing. A total of 97 morphologically distinct phototrophic, heterotrophic, and mixotrophic protists were revealed with the most diverse supertaxa SAR (59), Obazoa (9), and Excavates (14). The hidden diversity of protists (43 species) was a bit less than the active diversity (54 species). A taxonomic list and micrographs of cells for the observed protists are provided. The majority of species revealed are cosmopolitan or widespread in the northern sea waters. The vertical patterns of protist communities were absolutely different in 2018 and 2021. In July 2018, clearly distinct protist communities inhabited different layers of the lake. Bloom of cryptophyte Rhodomonas cf. baltica was detected in chemocline, whereas the maximum density of its grazers was observed in adjacent layers, mainly dinoflagellates Gymnodinium sp. and Scrippsiella trochoidea, as well as a ciliate Prorodon sp. In 2021 due to the recent mixing of lake and seawater, there were no distinct communities in the water column except the superficial 0–1 m layer of fresh water.